Nanoimaging of resonating hyperbolic polaritons in linear boron nitride antennas - F. J. Alfaro-Mozaz (Nature Portfolio, 2017)
Here, the authors report a near-field study of hyperbolic phonon polaritons in linear antennas made of hexagonal boron nitride. Infrared nanospectroscopy and nanoimaging experiments reveal sharp Fabry-Perot resonances with large quality factors, exhibiting atypical modal behaviour.